Cyclic dependency assessment of RBS moment connection in box-column. (February 2021) - Ghassemieh, M.; Hassani S., M.; Mirghaderi, S.R.
Abstract: In the present research, seismic performance of reduced beam section (RBS) moment connections in box-columns subjected to different loading protocols was evaluated through the experimental program and finite element study. The investigations performed in this research sought to explain the behavior and overall stability of the connection, strength degradation, panel zone performance, plasticity development at plastic hinges, and failure potentials. Also, since there are several loading protocols available in technical literature; another goal of this research was to investigate the difference and imposed demands by those protocols. In order to meet the research aims, laboratory specimens, along with the finite element models, were subjected to different loading protocols at the target value level, qualifying condition, and collapse threshold control. Based on the mentioned investigations, the performance parameters of the RBS moment connections in box-columns, as well as the demands and applied energies subjected to Western Asia, SAC, and ATC-24 loading protocols, were evaluated and compared. Graphical abstract: Unlabelled Image Highlights: Cyclicassessment of reduced beam section moment connection via experimental program and the finite element studies. Comparative investigation of the RBS connection at target value level, qualifying condition, and collapse threshold control. Effects of imposed demands on the specimens and the FEM models subjected to different cyclic loadings protocols. Controlling the behavior of RBS moment connection at collapse threshold control.